2012
DOI: 10.1124/dmd.112.045849
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Pharmacokinetics of Mangiferin in Conventional Rats, Pseudo-Germ-Free Rats, and Streptozotocin-Induced Diabetic Rats

Abstract: ABSTRACT:To clarify the role of the intestinal flora in the absorption and metabolism of mangiferin and to elucidate its metabolic fate and pharmacokinetic profile in diabetic rats, a systematic and comparative investigation of the metabolism and pharmacokinetics of mangiferin in conventional rats, pseudo-germ-free rats, and streptozotocin (STZ)-induced diabetic rats was conducted. Forty-eight metabolites of mangiferin were detected and identified in the urine, plasma, and feces after oral administration (400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 29 publications
6
53
1
1
Order By: Relevance
“…It is well known that DM induces morphological and/or functional complications that affect eyes, kidneys, gastrointestinal tract, peripheral, and autonomic nervous systems in DM patients [9][10][11] and DM animals [12][13][14][15][16]. Hence, these complications indicate that DM may alter the pharmacokinetic profiles of mangiferin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that DM induces morphological and/or functional complications that affect eyes, kidneys, gastrointestinal tract, peripheral, and autonomic nervous systems in DM patients [9][10][11] and DM animals [12][13][14][15][16]. Hence, these complications indicate that DM may alter the pharmacokinetic profiles of mangiferin.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these complications indicate that DM may alter the pharmacokinetic profiles of mangiferin. Liu et al [13] demonstrated a 2.79-and 2.35-fold increase in the plasma maximum concentration (C max ) and the area under the concentration-time curve from 0 to 24 h (AUC 0-24h ) of mangiferin in streptozotocin (STZ)-induced diabetic rats compared with those in conventional rats.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, species differences in gut microbiota (Rowland et al, 1986) make interspecies extrapolations difficult. Germ-free rats have been used to evaluate the role of bacterial microbiota in the metabolism of several compounds, including hesperidin, acetaminophen, and mangiferin (Jin et al, 2010;Lee et al, 2012;Liu et al, 2012). There are significant challenges in the maintenance and use of germ-free animals (Gordon and Pesti, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitations of large interspecies differences in microbiota composition and distribution have to be taken into consideration (Rowland et al, 1986;Sousa et al, 2008). Pseudo-germ free (pGF) rats can be created by treatment with broadspectrum antibiotics and have helped in elucidating the role of gut bacteria in the metabolism of drugs (Jin et al, 2010;Lee et al, 2012;Liu et al, 2012;Yoo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism and pharmacokinetic profiles of mangiferin have recently been examined [16][17][18]. Pharmacokinetic studies have indicated that mangiferin exhibits poor oral bioavailability (1.2%) when orally administered with the isolated compound directly [19].…”
Section: Introductionmentioning
confidence: 99%